Beginning rails 4 - Gamble, Adam; Carneiro, Cloves; Barazi, Rida Al (Apress Imprint: Apress, 2013)
Beginning Rails 4 is a book that will guide you from never having programmed with Ruby, to having a Rails application built and deployed to the web. You'll learn how to combine all the components of Rails to develop your own web applications. You will use test driven development to make sure your application works exactly like you expect. You will learn how to use Git for source control and best practice techniques to create applications like a pro. Essential, and often-missed, information on testing and learning to program with Ruby are also covered. This book is well suited for someone with little to no Ruby or Rails experience, or possibly even someone with no experience developing web applications at all. Beginning Rails 4 does assume a basic familiarity with the web and typical web terms, but doesn't require you to be an expert of these. This book will springboard your journey into web application development, and show you how much fun building web applications with Ruby on Rails can be. Learn to create Rails applications from the bottom up Learn the basics of the Ruby programming language Completely updated for Rails 4, including new information on turbo links, etc. Beginning Rails 4 gently guides you through designing your application, writing tests for the application, and then writing the code to make your application work as expected.